Przebieg kampanii wyborczej i wyborów z 4 czerwca 1989 roku w województwie zielonogórskim = The course of the electoral campaign and the election of june 4 1989 in Zielona Góra province - Pyrek, Sebastian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The decision of conducting the elections of june 4 1989 had been made during "the Round Table" talks which had been held in the Viceregal Palace (currently, the Presidential Palace) from February 6 to April 5 1989 by the government and the opposition. In the course of these talks, as pan of the passed reforms, it was established that on June 4 1989 semi-free Sejm elections and fully democratic Senate elections would be conducted.
Keywords: wybory parlamentarne; Polska - historia; 20 w.